1987
DOI: 10.1007/bf00218212
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation in organ cultures of bone marrow

Abstract: Bone formation in organ cultures of intact marrow fragments from mouse is described. Marrow explants were cultured on the top surface of a millipore filter at a gas-liquid interface. Observations with both light- and electron microscopes demonstrated the formation of a well-organised trabecular matrix lined with osteoblast-like cells. The tissue and cells were positive for alkaline-phosphatase activity. Large amounts of thick, well-banded collagen fibrils and matrix vesicles typical of those found in bone were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(20 citation statements)
references
References 10 publications
0
18
0
2
Order By: Relevance
“…Our that organ cultures of murine marrow, or marrow stromal cells, have bone-forming potential both in vivo (using diffusion chambers) and in vitro (7,40,41). These investigators further identified an osteogenic cell phenotype in a subpopulation of adherent bone marrow fibroblasts, localized near the (endosteal) bone surface (40,42).…”
Section: Resultsmentioning
confidence: 97%
“…Our that organ cultures of murine marrow, or marrow stromal cells, have bone-forming potential both in vivo (using diffusion chambers) and in vitro (7,40,41). These investigators further identified an osteogenic cell phenotype in a subpopulation of adherent bone marrow fibroblasts, localized near the (endosteal) bone surface (40,42).…”
Section: Resultsmentioning
confidence: 97%
“…A marrow stromal rather than hematopoietic origin of osteoblasts is supported by the induction of chondrogenesis and osteogenesis of bone marrow fragment or cell suspensions transplanted in vivo within diffusion chambers (30), by sequential histological examinations (31), and because bone marrow primary cultures can give rise to osteogenic, osteoblast-like stromal cell cultures (32,33), and cell lines (34). Histological and functional evidence in animal models suggest that osteoblasts can be defective in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that there are several sources of calcifying vascular cells in the arterial wall just as in bone where colony-forming unit fibroblasts (CFU-f) [3,4,29] as well as osteoblasts [23] participate in bone formation. Studies on the nature of the developmental lineages leading to the formation of bone cell types in humans, namely the osteoblast, osteoclast and CFU-f, suggest that osteoclasts may be the progeny of macrophages/monocytes [2,15,23] whereas osteoblast and CFU-f arise in some unknown manner from local mesenchymal cells and, as such, they do not express the panhaematopoietic cell surface antigen CD34 and fail to respond to haematopoietic growth factors [27,28].…”
Section: Discussionmentioning
confidence: 99%